Fundamento constitucional da incidência do imposto sobre produtos industrializados na importação: análise de julgados do STF e STJ acerca do tema - Souza, Mônica da Silva (2018)
Taxation on importation is the subject that more and more attention must be paid, considering, the importance to the Tax Law. The theme of this dissertation will address the constitutional basis of the collection of the Tax on industrialized products on importation. The study analyzes which constitutional principles, as well as the national treatment rule that underpin this collection. Import taxes will be observed under the view of the Federal Constitution as well as the National Tax Code of 1966, known as CTN, which have the extrafiscal and non-collection character. Tax collection, as the main source of public revenues, is very important for the State in promoting its public policies, however, it must respect the constitutional limits, so that its collection is carried out based on a plausible interpretation of the norms with the principle of legal certainty. The basis of the studies is specifically on the doctrinal and jurisprudential approach of the Supreme Courts (Supreme Federal Court and Superior Court of Justice) regarding taxation on imports, and it will certainly be covered the discussion about the collection of IPI on importation as well as the collection of the same tax on the exit of the same merchandise, without having undergone industrialization of industrial establishment or the like. And there is also the collection of ICMS on the same imported product that has the legitimacy of requirement based on Binding Summary 48 that was approved by the STF plenary on 05/27/2015. Since the issuance of EC 33/2001, the ICMS tax is levied on any and all imports, regardless of whether the person is a taxpayer or not, and therefore the ICMS tax is due. Just as the above grounds legalize the collection of ICMS on importation, the constitutional principles and the national treatment rule, are the basis for the systematic insertion of IPI on import, which will be further elaborated in the present work. There is no explicit provision in the Federal Constitution of 1988 authorizing the collection of the IPI on importation, but in the CTN, there is, for example, art. 46, which specifies the triggering event for the collection of said import tax. It is hoped academically to demonstrate the existing positions together with its foundations that authorize the systematic collection of the IPI on importation which falls on the equilibrium of isonomic taxation on both domestic and foreign products.